Konstruksi Kebahagiaan Dalam Bingkai Kecerdasan Spritual - Ernita Dewi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Every human must have longed for true happiness both physically and spiritually. Efforts to gain happiness will be done in various ways, collecting treasures, achieving success accross multiple life domain, seeking position and popularity. However, those are not guaranteed a person's happiness. Today, there are many people who poses wealth, success, popularity, but are infected by various mental diseases such as anxiety, stress, even feel alien to the surrounding world. It turns out that materialism alone cannot bring happiness. Only when the proper doses of spiritualism are mixed with the proper doses of materialism can we expect happiness. The real happiness lies in the aspect of human spirituality. Happiness will come only when someone achieve inner contentmen, close to God, always do good, intelligent to deal with life and consistently guided by the Koran and Hadith